Adsorption and removal of pentavalent antimony from water by biochar prepared from modified rosa roxburghii residue - Yong Dai; Shengmao Zhao; Ruyi Zheng (Frontiers in Environmental Science)
In order to investigate the adsorption properties of modified rosa roxburghii residue biochar to antimony (Sb) in water, the modified rosa roxburghii residue biochar (BC-FeOOH) was prepared from rosa roxburghii residue factory in Guizhou Processing plant. The adsorption characteristics of BC-FeOOH on Sb(V) in water were investigated by batch test experiments with different pH, biochar dosage and adsorption time. The results showed that the best adsorption effect of BC-FeOOH on antimony was achieved at the dosage of 0.05 g and pH 2.0, and the adsorption amount reached 5.7 mg/g. The results of adsorption kinetic modeling showed that the equilibrium time of the adsorption of BC-FeOOH on Sb(V) in water was in the range of 8–10 h, and the mechanism of adsorption was mainly chemical adsorption. Langmuir model can better describe the adsorption process of BC-FeOOH on Sb(V), and the surface adsorption process is monomolecular layer chemisorption. The experimental results showed that BC-FeOOH is a good adsorbent for Sb pollution remediation in water. This study provides n ew insights for the development of Sb contamination removal strategies in water and offers a new way for the resource utilization of prickly pear pomace.